The Association Between Maternal Feeding Patterns and Quality of Food Consumption with Stunting among Children Aged 18-24 Months in Bogor City, West Java, Indonesia: Hubungan Antara Pola Asuh Makan dan Kualitas Konsumsi Pangan dengan Stunting Anak Usia 18-24 Bulan di Kota Bogor, Jawa Barat, Indonesia - Yosepha Mextiany Ganella Gurang; Dodik Briawan; Yekti Widodo (Media Gizi Indonesia, 2023)
Healthy growth and development of children is the right of every child, both physically and mentally. Stunting is one of the features of delayed growth and development as a result of chronic malnutrition. The purpose of this study was to see the association maternal feeding patterns and quality of food consumption on stunting in children aged 18-24 months in Bogor City. This study uses a nested case-control study design by analyzing data from a cohort study of child development in five villages in Bogor. A total of 90 subjects aged 18-24 months were selected in this study consisted of 45 stunting subjects and 45 non-stunting subjects. The variables analyzed in this study maternal feeding patterns and quality of food consumption as measured by the energy density and other nutrients. Chi-square test was used to analyze the data. The results showed that there was a significant relationship between maternal feeding patterns (p=0.002) and stunting in children aged 18-24 months. There was a significant relationship between iron density measurement 2 (p=0.017) and calcium density measurement 2 (p=0.004) and stunting in children aged 18-24 months. Energy density and protein density did not show a significant relationship with stunting. Poor food parenting, as well as low intake of iron and calcium can increase the occurrence of stunting in children aged 18-24 months.